2002
DOI: 10.1021/jm020217z
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Quantitative Structure−Activity Relationship of 1,4-Dihydropyridines As Antitubercular Agents

Abstract: Three-dimensional quantitative structure-activity relationship (3D QSAR) methods, comparative molecular field analysis (CoMFA) and comparative molecular similarity indices analysis (CoMSIA), were applied on a series of 1,4-dihydropyridines possessing antitubercular activity. The study was performed using 33 compounds, in which 22 molecules were used for the derivation of the 3D QSAR models (training set) and 11 molecules were used to evaluate the predictive ability of the derived models (test set). Superimposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
62
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 32 publications
1
62
0
Order By: Relevance
“…In the pharmaceutical pipeline today, there are more than twelve 1,4-DHPs drug candidates commercially available in the global market, such as the nifedipine [2], felodipine [3], nicardipine [4] and etc., which were used to treat cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In the pharmaceutical pipeline today, there are more than twelve 1,4-DHPs drug candidates commercially available in the global market, such as the nifedipine [2], felodipine [3], nicardipine [4] and etc., which were used to treat cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The systematic structural modification of the 1,4-DHP ring yields different compounds used in the treatment of TB and cancer [3]. Recently, studies showed that 3,5-dicarbamoyl derivatives of 1,4-dihydropyridine (DHP) with lipophilic groups have considerable antitubercular activity against M. tuberculosis H37Rv [4][5][6][7][8]. It was also observed that esters or substituted isosters of pyridine and pyrazine carboxylic acids (such as tetrazoles) have been more active than the parent acids especially against resistant strains.…”
Section: Introductionmentioning
confidence: 99%
“…1,4-dihydropyridines as analogues of NADH coenzymes, such as nifedipine, nicardipine, amlodipine, and other related derivatives, are widely used as calcium channel blockers for the treatment of cardiovascular disorder including angina, hypertension and cardiac arrhythmias 3 . 1,4-Dihydropyridines are calcium antagonists 4 , antitubercular agents 5 , and neuropeptide Y Y1 receptor antagonists 6 . They possess method 12 , a one-pot condensation of an aldehyde with alkyl acetoacetate and ammonia, was presented.…”
Section: Introductionmentioning
confidence: 99%